THE CONDITION OF MAIN FACILITY IN THE VILLAGE OF FISH MARKETING PAKNINGASAL BUKITBATU DISTRICT OF BENGKALIS REGENCY IN RIAU PROVINCE - Alpin Septiyan Harahap; Jonny Zain; Ronald M. Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in December 2016 in the village Pakningasal Bukitbatu District of Bengkalis in Riau province. The purpose of this study was to determine the conditions under which the basic amenities harbor dock and pool required by the fishermen in the village of Fish Marketing Sites Pakningasal. The method used in this study is a survey method that is by direct observation and collect information about the basic amenities and activities at The Village Fish Marketing Pakningasal. From the results of research conducted marketing place has 10 units fish-shaped pier jetty.The dock has a respective length of 3-7 m and has a height also varies between of 1 - 1.5 m from the seabed to the construction made of wood with a width of from 0.3 to 0.6 m. While the existing harbor pool area at The Village Fish Marketing Pakningasal not have enough wide and shallow. Extensive pool of currently available port is ± 800 m2 with a depth varying port basin.Keywords: Condition, Pier, Harbor Swimming